Axillary apocrine carcinoma with benign apocrine tumours: a case report involving a pathological and immunohistochemical study and review of the literature. Issue 7 (23rd June 2005) - Miyamoto, T; Hagari, Y; Inoue, S; Watanabe, T; Yoshino, T
Abstract : Background: Apocrine carcinoma is rare and often occurs in the axilla. This is the second apocrine carcinoma arising in bilateral axillae with associated apocrine hyperplasia to be reported. Aims/Methods: Because benign apocrine tumours may be precursors of cancer, this case was investigated immunohistochemically and histologically, and a literature (English and Japanese) review undertaken of cases with coexistent malignant and benign apocrine tumours in the axilla to elucidate the relation between apocrine carcinoma and benign apocrine tumours. Results: Only four cases of axillary apocrine carcinoma with benign apocrine tumours were identified in the literature. In each case, benign apocrine hyperplasia was situated within and surrounding the adenocarcinomatous nests. Staining for epithelial membrane antigen revealed three patterns: (1) poorly differentiated tumour cells showing strong cytoplasmic staining; (2) combined luminal surface and cytoplasmic staining of glandular cells; and (3) a strongly positive lineal staining pattern at the luminal membrane surface, comprising one or two apocrine hyperplastic secretory cells. The basal lesions of apocrine hyperplasia were strongly positive for α smooth muscle actin, whereas the periphery of adenomatous lesions showed weaker positive staining, even though the periphery of adenocarcinomatous lesions was negative. Conclusions: All five apocrine carcinomas with benign apocrine tumours occurred in elderly Japanese men who had bilateral benign apocrine tumours even if affected by unilateral axillary apocrine carcinoma. The immunohistochemical results support the notion that apocrine hyperplasia is a precursor of cancer and that apocrine carcinoma, adenoma, and hyperplasia may be successive steps in the linear progression to carcinoma.